Conceptual modeling and characterization of Puga geothermal reservoir, Ladakh, India. (March 2018) - Jha, Shibani K.; Puppala, Harish
Highlights: Conceptual model of Puga geothermal reservoir as block heterogeneity. Spatial variation of thermo-hydro-geological parameters after block heterogeneity. Spatial variation of equilibrium temperature after block heterogeneity. Identification of areal extent of possible heat source. Abstract: Evaluation of a potential geothermal reservoir depends on the conceptual model which governs fluid flow and heat transfer in the reservoir. Knowing the spatial variation of reservoir parameters is essential to develop a conceivable and explicable conceptual model. Lack of deep reservoir characteristics impaired the development of conceptual model for Puga geothermal field, India. This study proposes a methodology to develop a conceptual model of Puga geothermal field. The proposed methodology utilizes the resistivity model developed by National Geophysical Research Institute as preliminary data. The conceptual model developed in this study, maps the spatial variation of thermo-hydro-geological properties of Puga reservoir. The mapped properties of the reservoir are porosity, thermal conductivity, specific heat, radioactive heat capacity, density and permeability of reservoir. Furthermore, lateral extent of the possible heat source and spatial variation of steady state temperature of the reservoir are also estimated. The estimated reservoir temperature from the conceptual model of Puga geothermal field is in agreement with temperature interpretations of Na/K and Na-K-Ca geothermometer studies. The resulting conceptual model will further aid in the operational phase of reservoir development like volumetric assessment of reservoir potential and reservoir potential estimation under various extraction configuration.